RC / HA / dAM lyophilized powder for promoting lymphatic vessel regeneration and method of preparation thereof
Patent Information
- Application Number
- CN202611342299.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-16
AI Technical Summary
[0007]本申请提供了一种用于促进淋巴管再生的RC/HA/dAM冻干粉及其制备方法,解决了脱细胞羊膜难以以适宜的材料形态充分发挥促进淋巴管再生作用的问题
本申请将脱细胞羊膜与交联重组胶原蛋白/透明质酸钠纤维膜进行复合,并进一步将所得RC/HA/dAM复合膜制备为分散于透明质酸钠冻干基质中的复合微粒,使原本以膜状形态存在的脱细胞羊膜能够以更适于局部应用的冻干粉形式使用。交联重组胶原蛋白/透明质酸钠纤维网络能够为脱细胞羊膜提供一定的结构支撑,并有利于提高复合材料在颗粒化后的结构稳定性;外部透明质酸钠冻干基质则有利于对RC/HA/dAM复合微粒进行分散和承载。由此,所得RC/HA/dAM冻干粉能够较好地发挥脱细胞羊膜的促淋巴管再生作用。实验结果表明,本申请提供的RC/HA/dAM冻干粉具有良好的生物相容性,并能够促进淋巴管内皮细胞的增殖、迁移和成管,同时能够在动物体内显著促进淋巴管长入,具有良好的淋巴管修复与再生应用潜力。
Smart Images

Figure CN122912187A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of biomedical technology, specifically to an RC / HA / dAM lyophilized powder for promoting lymphatic vessel regeneration and its preparation method. Background Technology
[0002] The lymphatic system is an important component of the human circulatory system, consisting of capillary lymphatic vessels and collecting lymphatic vessels. Lymphatic vessels have high permeability and unidirectional transport characteristics, enabling them to absorb and drain tissue fluid and macromolecules, playing a crucial role in maintaining tissue fluid homeostasis, lipid absorption and transport, and immune cell transport. When lymphatic vessels are damaged or regenerate insufficiently, it can lead to impaired lymphatic drainage, further causing problems such as lymphedema, chronic inflammation, impaired wound healing, and limited tissue repair. Therefore, promoting the repair and regeneration of lymphatic vessels at the site of injury is of great significance for improving local tissue fluid return, promoting inflammation resolution, and repairing damaged tissue.
[0003] In recent years, with the development of tissue engineering and regenerative medicine, regulating the local microenvironment through biomaterials to promote lymphangiogenesis has gradually become an important research direction in the field of tissue repair. Existing research shows that lymphangiogenesis is closely related to the proliferation, migration, and tube formation of lymphatic endothelial cells, and is simultaneously regulated by the local extracellular matrix structure and biological microenvironment. Based on this, studies have used materials such as collagen scaffolds, hydrogels loaded with cell-derived exosomes, and multi-component composite scaffolds to promote lymphangiogenesis, demonstrating certain tissue repair effects in applications such as skin injury, osteoarthritis, and bone defect repair.
[0004] However, some existing lymphatic regeneration-promoting materials rely on exogenous cells, bacterial strains, cell-derived components, or other bioactive substances. Their material composition and preparation systems are relatively complex, and there is still room for improvement in terms of material stability, biosafety, and ease of clinical application. Therefore, constructing lymphatic regeneration-promoting systems using materials with good biocompatibility and natural extracellular matrix characteristics has significant research and application value.
[0005] Decellularized amniotic membrane (dAM) is an extracellular matrix material obtained by decellularizing natural amniotic membrane. It retains the original extracellular matrix structure of the amniotic membrane well and exhibits good biocompatibility, showing promising application potential in wound repair and tissue regeneration. Compared to artificial materials with relatively simple compositions, decellularized amniotic membrane provides a natural extracellular matrix environment, offering favorable conditions for cell adhesion, migration, and tissue repair. Currently, decellularized amniotic membrane is mainly used in the form of membrane materials or tissue repair scaffolds for wound coverage and tissue repair. Its application in promoting lymphatic vessel repair and regeneration, as well as its suitability for local drug delivery, still has room for further development.
[0006] Therefore, it is necessary to further develop lymphatic regeneration-promoting materials based on decellularized amnion so that they can be better applied to sites of lymphatic vessel damage and play a role in promoting lymphatic vessel repair and regeneration. Summary of the Invention
[0007] This application provides an RC / HA / dAM lyophilized powder for promoting lymphatic vessel regeneration and its preparation method, which solves the problem that decellularized amniotic membrane is difficult to fully exert its effect of promoting lymphatic vessel regeneration in a suitable material form.
[0008] In a first aspect, this application provides an RC / HA / dAM lyophilized powder for promoting lymphatic vessel regeneration, comprising: a sodium hyaluronate lyophilized matrix, and RC / HA / dAM composite microparticles dispersed in the sodium hyaluronate lyophilized matrix; The RC / HA / dAM composite microparticles are obtained by freeze-drying and freeze-milling of an RC / HA / dAM composite membrane. The RC / HA / dAM composite membrane comprises a first decellularized amnion, a cross-linked recombinant collagen / sodium hyaluronate fiber membrane, and a second decellularized amnion arranged sequentially, wherein the first decellularized amnion and the second decellularized amnion are chemically cross-linked with the cross-linked recombinant collagen / sodium hyaluronate fiber membrane, respectively.
[0009] According to this application, by combining decellularized amniotic membrane with cross-linked recombinant collagen / sodium hyaluronate fiber membrane, and further preparing the resulting RC / HA / dAM composite membrane into composite microparticles dispersed in a sodium hyaluronate freeze-dried matrix, the decellularized amniotic membrane can be used in a material form more suitable for local application at the site of lymphatic vessel injury, and it is beneficial to maintain the structural stability and continuous effect of the composite material in the local environment, thereby effectively promoting the repair and regeneration of lymphatic vessels.
[0010] Specifically, during their research on the use of decellularized amniotic membrane for lymphatic vessel repair and regeneration, the inventors discovered that decellularized amniotic membrane possesses excellent biocompatibility and a natural extracellular matrix structure, and can have a beneficial effect on lymphatic vessel endothelial cells, thus showing potential for promoting lymphatic vessel regeneration. However, decellularized amniotic membrane typically exists in a membrane-like form, making direct application inconvenient for some lymphatic vessel injuries, especially those located deep or with irregular shapes. Therefore, the inventors considered transforming the decellularized amniotic membrane from a membrane-like material into a granular material to improve its flexibility for local application.
[0011] The inventors further recognized that decellularized amnion, being a naturally biodegradable extracellular matrix material, undergoes further fragmentation when freeze-dried and pulverized into smaller particles. This increases the material's contact with surrounding body fluids and the degradation environment, potentially reducing its structural stability in the local environment and hindering its ability to continuously promote lymphatic vessel regeneration. Therefore, instead of directly pulverizing the decellularized amnion, the inventors considered using fibrous extracellular matrix materials to composite and stabilize it before granulation.
[0012] In selecting the fiber material, the inventors considered that recombinant collagen has good biocompatibility and can form a fibrous structure similar to the natural extracellular matrix, making it suitable as a fibrous framework to support the decellularized amnion. However, fibrous membranes formed solely from recombinant collagen are also relatively easily degraded protein materials, and their structural stability remains somewhat limited during subsequent pulverization and localized application. Therefore, the inventors further introduced sodium hyaluronate into the recombinant collagen fiber system, allowing it to co-form a fibrous membrane with the recombinant collagen. Sodium hyaluronate has good hydrophilicity and biocompatibility and is an important component of the natural extracellular matrix. Its introduction helps improve the hydration environment of the recombinant collagen fiber network and participates in the formation of a composite network during subsequent chemical cross-linking, thereby improving the structural stability of the fibrous membrane in an aqueous environment. Thus, recombinant collagen mainly provides the fibrous framework and extracellular matrix-like structure, while sodium hyaluronate is used to regulate the hydrophilicity and cross-linking stability of the fiber network. The combination of the two forms a fibrous membrane structure more suitable for composite with the decellularized amnion.
[0013] Furthermore, the inventors positioned the cross-linked recombinant collagen / sodium hyaluronate fiber membrane between two layers of decellularized amnion, and chemically cross-linked the decellularized amnion on both sides with the fiber membrane, thereby forming an integral RC / HA / dAM composite membrane. This composite structure allows for a more stable bond between the decellularized amnion and the cross-linked fiber network, ensuring that the resulting composite membrane, after subsequent freeze-drying and freeze-milling, still forms composite microparticles containing both the decellularized amnion and the cross-linked recombinant collagen / sodium hyaluronate fiber network. Compared to directly pulverizing the decellularized amnion, this method helps reduce the tendency for rapid structural damage after granulation, allowing the decellularized amnion to maintain a relatively continuous function in the local environment.
[0014] Building upon this, the inventors further discovered that when the RC / HA / dAM composite microparticles obtained through freeze-milling are directly added to an aqueous medium, they are prone to water absorption, aggregation, or sedimentation, making it difficult to form a uniform and stable dispersion system. This is not conducive to the uniform application of the microparticles to the lymphatic vessel damage site. Considering that sodium hyaluronate has good hydrophilicity and can form an aqueous environment with a certain viscosity, the inventors further dispersed the RC / HA / dAM composite microparticles in a sodium hyaluronate system and then freeze-dried them, so that the composite microparticles are dispersed in a freeze-dried matrix formed by sodium hyaluronate. The freeze-dried sodium hyaluronate matrix can, on the one hand, support and separate the composite microparticles in the freeze-dried state, and on the other hand, it can form a hydration environment suitable for the dispersion of the composite microparticles after rehydration during use, thereby facilitating the more uniform application of the composite microparticles to the affected area.
[0015] It is worth noting that this application introduces sodium hyaluronate both inside and outside the RC / HA / dAM composite microparticles, but their structural levels and functions differ. The sodium hyaluronate inside the composite microparticles, together with recombinant collagen, forms a fibrous network and participates in the formation of the decellularized amniotic membrane composite structure, primarily improving the hydration and structural stability of the internal fibrous network. The sodium hyaluronate outside the composite microparticles forms a lyophilized matrix, mainly used to support and disperse the resulting composite microparticles, and to provide a suitable aqueous environment after rehydration. The two portions of sodium hyaluronate form mutually supportive hydrophilic environments inside and outside the material, allowing the resulting lyophilized powder to maintain the RC / HA / dAM composite structure inside the microparticles and to maintain the dispersed state of the composite microparticles during use. This enables the decellularized amniotic membrane to fully and relatively continuously promote lymphatic vessel regeneration at the affected area.
[0016] Based on the above design, the inventors constructed a lyophilized powder system with RC / HA / dAM composite microparticles as the main active unit and sodium hyaluronate as the carrier. Subsequent experimental results showed that the lyophilized powder has good biocompatibility, can promote the proliferation, migration, and tube formation of lymphatic endothelial cells, and can promote lymphatic vessel ingrowth in animals, indicating that the above material structure and dosage form design can effectively exert the effect of decellularized amnion in promoting lymphatic vessel repair and regeneration.
[0017] It should be noted that decellularized amnion and recombinant collagen have meanings known in the art. As an example, the above features will be explained accordingly below.
[0018] [Acellular amnion] The amnion described in this application is the innermost layer of the placenta, typically appearing as a transparent membrane without blood vessels, nerves, or lymphatic vessels, and possessing a certain degree of toughness. The amnion is rich in extracellular matrix components such as collagen, laminin, and fibronectin, and can retain certain types of growth factors and cytokines, thus exhibiting good biocompatibility and a basis for tissue repair applications.
[0019] The natural amnion consists of an epithelial cell layer, a basement membrane, a matrix layer, a fibroblast layer, and a spongy layer. The natural amnion can be divided into two sides: the epithelial side (after removing the epithelial cell layer, it becomes the side with the basement membrane), and the stromal side (also known as the villi side), which is the side with the spongy layer. By processing the natural amnion to remove the epithelial cell layer, we obtain acellular amnion, which consists of the basement membrane, matrix layer, fibroblast layer, and spongy layer; or by removing both the epithelial cell layer and the fibroblast layer, we obtain completely acellular amnion, which consists of the basement membrane, matrix layer, and spongy layer.
[0020] The decellularized amnion (dAM) described in this application includes deepithelialized amnion and wholly decellularized amnion. In some embodiments, the first and second decellularized amnions included in the composite amnion material are both wholly decellularized amnions to minimize the risk of antigen reactions after implantation.
[0021] The decellularized amniotic membrane used in this application can be obtained by the following exemplary method: Thaw the cryopreserved amniotic membrane, remove it from the surgical tape, place it in a culture dish, and wash it three times with purified water. Prepare a neutral protease (Maclean's, Dispase BR, 50 u / mg) working solution in 0.1 wt% serum-free medium or PBS. Add the enzyme solution to the centrifuge tube containing the amniotic membrane, ensuring the membrane is completely immersed. Incubate at 4°C for 6 hours or at room temperature for half an hour. After incubation, scrape off the amniotic epithelium, place the amniotic membrane in PBS, manually scrape off the amniotic epithelial cells until the amniotic membrane is transparent, and then wash it three times with purified water.
[0022] In some embodiments, the amnion used to prepare the decellularized amnion is freshly obtained. In some embodiments, the amnion used to prepare the decellularized amnion is derived from bovine, equine, suidae, canine, feline, rodent, or primate animals, for example, from humans.
[0023] [Recombinant Collagen] Collagen is a general term for a class of biological macromolecular proteins. It is one of the main components of animal connective tissue and the most abundant and widely distributed functional protein in mammals. Collagen is widely present in skin, bones, joints, and hair, playing a supporting, repairing, and anti-aging role. Human collagen is classified into more than 28 types based on tissue location, physiological function, and molecular structure, with type I, type II, and type III collagen being the most prevalent. The collagen in human skin is mainly type I and type III collagen.
[0024] Currently, most collagen used in biomedical applications still comes from animal sources, such as the skin, tendons, and bones of cattle, pigs, and birds. Animal-derived collagen has inherent drawbacks: it exhibits batch-to-batch variability in quantity and quality, may trigger immunogenic reactions, and carries the risk of transmitting animal viruses and prions.
[0025] To address the aforementioned issues, DNA recombination technology can be used to obtain collagen with human-like characteristics through recombinant expression; this is known as recombinant collagen. Recombinant collagen includes recombinant human collagen, recombinant humanized collagen, and recombinant human-like collagen. Currently, many recombinant expression systems are being used for the recombinant expression of collagen, such as those in E. coli, yeast, animal cells, transgenic animals, and transgenic plants.
[0026] Recombinant human collagen (RC) is prepared using DNA recombination technology. It expresses the complete sequence of a specific type of human collagen gene in eukaryotic cells and is structurally identical to natural collagen, possessing a triple helix structure. Recombinant humanized collagen is a fragment of an amino acid sequence encoded by a specific type of human collagen gene, prepared using DNA recombination technology, or a combination of functional fragments containing human collagen. Recombinant human-like collagen is a designed and modified amino acid sequence or fragment thereof, prepared using DNA recombinant collagen technology, encoded by a specific gene, or a combination of such functional amino acid sequence fragments. Its gene coding sequence or amino acid sequence shows low homology to the gene coding sequence or amino acid sequence of human collagen.
[0027] Among the three types of recombinant collagen mentioned above, recombinant humanized collagen is obtained by using the collagen gene sequence of human skin as the original sequence, optimizing and screening for advantageous components (such as those with high water solubility, high bioactivity, and / or good permeability), and then performing codon optimization and splicing recombination. Recombinant humanized collagen has a higher homology to human collagen than recombinant human-like collagen, which can reduce the "foreign body reaction" of implants. Therefore, in some embodiments, this application uses recombinant humanized collagen.
[0028] In some embodiments, the cross-linked recombinant collagen / sodium hyaluronate fiber membrane is obtained by electrospinning a spinning solution containing recombinant collagen and sodium hyaluronate to form a recombinant collagen / sodium hyaluronate fiber membrane, followed by chemical cross-linking of the fiber membrane.
[0029] In some of the above embodiments, recombinant collagen can form a membrane with a fibrous structure, and sodium hyaluronate has good hydrophilicity and biocompatibility. Electrospinning the two together is beneficial for forming a composite fiber membrane that combines fibrous structure and hydration properties. Further chemical cross-linking can improve the structural stability of the fiber membrane in an aqueous environment, making it more suitable for subsequent composite with decellularized amnion membrane.
[0030] In some embodiments, the molecular weight of the first sodium hyaluronate is less than 10 kDa; the concentration of recombinant collagen in the spinning solution is 15-25% w / w, the concentration of the first sodium hyaluronate is 3-5% w / w, and the solvent of the spinning solution is a 40-60% v / v aqueous ethanol solution.
[0031] In some of the above embodiments, by controlling the molecular weight of the first sodium hyaluronate and the ratio of recombinant collagen, the first sodium hyaluronate, and the ethanol aqueous solution, it is beneficial to obtain a spinning solution with a more uniform composition and suitable spinnability, and to form a more stable recombinant collagen / sodium hyaluronate fiber membrane. Using a lower molecular weight for the first sodium hyaluronate facilitates its uniform mixing with the recombinant collagen in the spinning system and reduces its adverse effects on the viscosity of the spinning solution and the fiber-forming process. Within the above concentration range, the recombinant collagen can provide the main fiber-forming backbone, while the first sodium hyaluronate acts as a hydrophilic extracellular matrix component dispersed in the fiber system, thereby facilitating subsequent cross-linking treatment and composite with decellularized amnion.
[0032] In some embodiments, the electrospinning is performed using an electrospinning machine with a positive voltage of 20kV, a negative voltage of -5kV, a feeding speed of 0.05 to 0.10 mm / min, and a receiving distance of 10 to 15 cm.
[0033] In some embodiments, the recombinant collagen / sodium hyaluronate fiber membrane is crosslinked with EDC / NHS, wherein the molar ratio of EDC to NHS is 1:(0.8-1.2), and the crosslinking time is 20-28 h.
[0034] In some of the above embodiments, EDC / NHS can promote cross-linking between carboxyl and amino groups in the recombinant collagen / sodium hyaluronate fiber membrane, thereby improving the structural stability of the fiber membrane in an aqueous environment. Controlling the molar ratio of EDC to NHS and the cross-linking time within the aforementioned ranges is beneficial for obtaining a more stable cross-linked fiber network while maintaining the overall structure and material compatibility of the fiber membrane, providing a suitable membrane foundation for subsequent composite with decellularized amnion membrane.
[0035] In some implementations, anhydrous ethanol can be used to dissolve EDC and NHS, with a total concentration of 0.2 mol / L for EDC and NHS.
[0036] In some embodiments, the second sodium hyaluronate used to form the lyophilized sodium hyaluronate matrix has a molecular weight of less than 1000 kDa, and the mass ratio of the RC / HA / dAM composite microparticles to the second sodium hyaluronate is (8-10):1.
[0037] In some embodiments, the second sodium hyaluronate used to form the lyophilized sodium hyaluronate matrix has a molecular weight of less than 1000 kDa, and the mass ratio of the RC / HA / dAM composite microparticles to the second sodium hyaluronate is (8-10):1.
[0038] In some of the above embodiments, the second sodium hyaluronate is mainly used to form the external freeze-dried matrix supporting the RC / HA / dAM composite microparticles. It should be noted that this application does not simply use the second sodium hyaluronate as a thickening or suspending component, but rather uses sodium hyaluronate both inside and outside the RC / HA / dAM composite microparticles. Through the functional division of different molecular weight sodium hyaluronates at different structural levels, a continuous hyaluronic acid hydration environment is formed from the inside to the outside of the composite microparticles.
[0039] Specifically, the first sodium hyaluronate has a lower molecular weight, enabling it to better integrate with recombinant collagen into the electrospinning system and participate in the formation of the RC / HA fiber network, thus distributing the hyaluronic acid component within the RC / HA / dAM composite microparticles. The second sodium hyaluronate has a higher molecular weight than the first sodium hyaluronate, making it more suitable for forming a continuous hydrated matrix on the outside of the composite microparticles. Because the first and second sodium hyaluronates share the same hyaluronic acid backbone, the composite microparticles exhibit good material compatibility both internally and externally. During the rehydration process of the lyophilized powder, the external second sodium hyaluronate forms a continuous hydrated phase while simultaneously creating a continuously hydrated environment with the first sodium hyaluronate contained within and on the surface of the composite microparticles. This facilitates thorough wetting and uniform dispersion of the RC / HA / dAM composite microparticles, reducing interfacial incompatibility between the composite microparticles and the external carrier due to differences in material properties.
[0040] Therefore, the first sodium hyaluronate mainly participates in the construction of the internal fibrous network and composite interface of the RC / HA / dAM composite microparticles, while the second sodium hyaluronate mainly forms the continuous hydration matrix on the outside of the composite microparticles. Both, while maintaining the same material composition, act on the inside and outside of the microparticles respectively, resulting in a hyaluronic acid-rich microenvironment with compatible internal and external components after rehydration of the lyophilized powder. This structure facilitates better hydration and distribution of the RC / HA / dAM composite microparticles at the affected area, and allows the decellularized amniotic membrane and the RC / HA composite extracellular matrix to fully contact the surrounding lymphatic endothelial cells and tissues. This, in turn, promotes the sustained proliferation, migration, and tubular formation of lymphatic endothelial cells, further promoting lymphatic vessel repair and regeneration.
[0041] In some embodiments, the cross-linked recombinant collagen / sodium hyaluronate fiber membrane is attached to the matrix surface of both the first decellularized amnion and the second decellularized amnion. Based on the above embodiments, the matrix surface of the decellularized amnion is rougher than the epithelial surface, allowing for better integration with the fiber membrane.
[0042] Secondly, this application provides a method for preparing RC / HA / dAM lyophilized powder for promoting lymphatic vessel regeneration, comprising the following steps: S1: The cross-linked recombinant collagen / sodium hyaluronate fiber membrane is placed between the first decellularized amnion and the second decellularized amnion, and is pressed in a chemical cross-linking system to cross-link the decellularized amnion with the cross-linked recombinant collagen / sodium hyaluronate fiber membrane to obtain the RC / HA / dAM composite membrane. S2: The RC / HA / dAM composite membrane is freeze-dried and then freeze-milled to obtain RC / HA / dAM composite microparticles; S3: After dispersing the RC / HA / dAM composite microparticles in a second sodium hyaluronate solution to form a suspension, the suspension is freeze-dried to obtain RC / HA / dAM freeze-dried powder for promoting lymphatic vessel regeneration.
[0043] According to this application, by first cross-linking a cross-linked recombinant collagen / sodium hyaluronate fiber membrane with two layers of decellularized amnion, and then freeze-drying and freeze-milling the resulting RC / HA / dAM composite membrane, the membrane material can be transformed into composite microparticles while maintaining a relatively stable composite relationship between the decellularized amnion and the cross-linked fiber network. Furthermore, dispersing the obtained RC / HA / dAM composite microparticles in a second sodium hyaluronate solution and freeze-drying them helps to form a more uniform freeze-dried dispersion system, thereby obtaining RC / HA / dAM freeze-dried powder suitable for local applications.
[0044] Specifically, in step S1, the cross-linked recombinant collagen / sodium hyaluronate fiber membrane is located between the first and second decellularized amnions. Under the chemical cross-linking system and compression, this facilitates increased contact between the fiber membrane and the two decellularized amnions, promoting the formation of a stable composite structure. In step S2, the obtained RC / HA / dAM composite membrane is first freeze-dried and then freeze-milled. This allows the membrane material to be transformed into smaller composite microparticles at lower temperatures, facilitating subsequent dispersion and localized application. In step S3, the RC / HA / dAM composite microparticles are further dispersed in a second sodium hyaluronate solution to form a suspension before freeze-drying. This allows the second sodium hyaluronate to form a matrix that supports the composite microparticles during freeze-drying, improving the dispersion of the composite microparticles and facilitating subsequent rehydration of the resulting freeze-dried powder.
[0045] Through the continuous combination of the above steps, the originally membrane-like decellularized amniotic membrane can be transformed into a freeze-dried powder system composed of RC / HA / dAM composite microparticles and sodium hyaluronate freeze-dried matrix. During the material morphology transformation process, the composite structure between the decellularized amniotic membrane and the cross-linked recombinant collagen / sodium hyaluronate fiber network is maintained, thereby making the obtained material more suitable for local application and for promoting lymphatic vessel repair and regeneration.
[0046] In some embodiments, the cross-linked recombinant collagen / sodium hyaluronate fiber membrane can be prepared with reference to the contents described in any embodiment of the first aspect.
[0047] In some embodiments, S1 includes placing a cross-linked recombinant collagen / sodium hyaluronate fiber membrane between a first decellularized amnion and a second decellularized amnion, and then placing it into an EDC / NHS cross-linking system for cross-linking under mechanical compression for 40–60 h; the molar ratio of EDC to NHS is 1:(0.8–1.2).
[0048] In some of the above embodiments, by maintaining sufficient contact between the cross-linked recombinant collagen / sodium hyaluronate fiber membrane and the decellularized amnions on both sides under mechanical pressing, and by utilizing EDC / NHS to promote cross-linking between carboxyl and amino groups at the interface, the bonding stability between the three layers of materials is improved. Controlling the cross-linking time and the molar ratio of EDC to NHS within the aforementioned range ensures a relatively stable connection in the composite membrane while avoiding excessively strong cross-linking conditions that could adversely affect the original extracellular matrix structure of the decellularized amnion, thereby obtaining a structurally more complete RC / HA / dAM composite membrane.
[0049] In some implementations, EDC and NHS can be dissolved in PBS buffer, with a total concentration of 0.2 mol / L for EDC and NHS.
[0050] In some embodiments, in S2, after the RC / HA / dAM composite membrane is freeze-dried, it is cut into fragments smaller than 6 mm and then cryogenically ground. The cryogenic grinding includes pre-cooling for 8 to 15 minutes and grinding 8 to 15 times at a rate of 8 to 15 cps, with each cycle running for 0.5 to 1.5 minutes and cooling for 2 to 4 minutes.
[0051] In some of the above embodiments, the freeze-dried RC / HA / dAM composite film is first sheared into smaller fragments, which helps improve the processing uniformity in the subsequent freeze-milling process. By pre-cooling and using intermittent freeze-milling, the material can be repeatedly subjected to mechanical action at a lower temperature, which is beneficial for preparing the composite film into composite microparticles with smaller and more uniform particle size. Controlling the pre-cooling time, milling rate, number of cycles, and single run and cooling time within the above ranges helps to balance milling efficiency and composite material structure preservation, providing a suitable particle basis for the subsequent dispersion of composite microparticles in the second sodium hyaluronate system.
[0052] In some embodiments, in S3, the mass ratio of RC / HA / dAM composite microparticles to second sodium hyaluronate in the suspension is (8-10):1, and the total solid concentration is 15-25 mg / mL.
[0053] In some of the above embodiments, by controlling the mass ratio of RC / HA / dAM composite microparticles to the second sodium hyaluronate and the total solids concentration of the suspension, it is beneficial to maintain a relatively uniform dispersion of the composite microparticles in the second sodium hyaluronate system, while ensuring that the suspension has a suitable system concentration, facilitating subsequent packaging and freeze-drying. The aforementioned ratio and total solids concentration also achieve a good balance between the content of the composite microparticles and the dispersion and carrying capacity of the second sodium hyaluronate, thereby contributing to obtaining a uniformly composed RC / HA / dAM freeze-dried powder.
[0054] Thirdly, this application provides the use of the RC / HA / dAM lyophilized powder according to any embodiment of the first aspect or the RC / HA / dAM lyophilized powder prepared according to the method according to any embodiment of the second aspect in the preparation of a formulation for promoting lymphatic vessel regeneration.
[0055] According to this application, the RC / HA / dAM lyophilized powder can be used for lymphatic vessel repair and regeneration. Experimental results show that the RC / HA / dAM lyophilized powder has good biocompatibility and can promote the proliferation, migration, and tube formation of lymphatic vessel endothelial cells. Further animal experiments show that the RC / HA / dAM lyophilized powder can promote lymphatic vessel ingrowth at the material implantation site, indicating that it has the effect of promoting lymphatic vessel regeneration and can be used to prepare formulations that promote lymphatic vessel repair and regeneration.
[0056] Compared with the prior art, the beneficial effects of this application are at least as follows: This application combines decellularized amniotic membrane with a cross-linked recombinant collagen / sodium hyaluronate fiber membrane, and further prepares the resulting RC / HA / dAM composite membrane into composite microparticles dispersed in a sodium hyaluronate lyophilized matrix. This allows the decellularized amniotic membrane, originally existing in a membrane form, to be used in a lyophilized powder form more suitable for local application. The cross-linked recombinant collagen / sodium hyaluronate fiber network provides structural support for the decellularized amniotic membrane and helps improve the structural stability of the composite material after granulation; the external sodium hyaluronate lyophilized matrix facilitates the dispersion and support of the RC / HA / dAM composite microparticles. Therefore, the resulting RC / HA / dAM lyophilized powder can effectively promote lymphatic vessel regeneration of the decellularized amniotic membrane. Experimental results show that the RC / HA / dAM lyophilized powder provided in this application has good biocompatibility and can promote the proliferation, migration, and tube formation of lymphatic endothelial cells. It also significantly promotes lymphatic vessel ingrowth in animals, demonstrating good potential for lymphatic vessel repair and regeneration. Attached Figure Description
[0057] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.
[0058] Figure 1 Figure 1 shows the construction and material characterization results of the RC / HA / dAM lyophilized powder of this application; where, Figure 1 A is a schematic diagram of the preparation process of RC / HA / dAM lyophilized powder; Figure 1 B shows scanning electron microscope images of HA lyophilized powder, RC / HA lyophilized powder, dAM lyophilized powder, and RC / HA / dAM lyophilized powder. Figure 1 C Figure 1 D、 Figure 1 Figure E shows the particle size analysis results for RC / HA particles, dAM particles, and RC / HA / dAM composite particles, respectively.
[0059] Figure 2 The figure shows the effects of different materials on the cell compatibility, proliferation, and migration of human lymphatic endothelial cells (hLECs); among them, Figure 2 Figure A shows the TUNEL staining results of hLECs after treatment in the Control group, HA group, RC / HA group, dAM group, and RC / HA / dAM group. Figure 2 B shows the staining results of live / dead hLECs after treatment in each group; Figure 2 C shows the results of hLECsEdU immunofluorescence staining after treatment in each group; Figure 2 D shows the staining results of the hLECs Transwell migration assay after each group of treatments; Figure 2 E is a graph showing the statistical results of the proportion of EdU-positive cells in each group of hLECs; Figure 2 F is a graph showing the statistical results of the number of migrating hLECs in each group.
[0060] Figure 3 The figure shows the results of the influence of different materials on the migration and tube-forming ability of hLECs; among them, Figure 3 Figure A shows the scratch test results of hLECs after treatment in the Control group, HA group, RC / HA group, dAM group, and RC / HA / dAM group. Figure 3 Figure B shows the tube formation results of hLECs after each treatment group; Figure 3 C is a graph showing the statistical results of the hLECs scratch migration area for each group; Figure 3 D is a statistical result of the number of hLECs pipe nodes in each group; Figure 3 E is a statistical result of the total length of hLECs in each group.
[0061] Figure 4 The diagram shows the results of different materials promoting lymphatic vessel regeneration in mice; among them, Figure 4 A is a schematic diagram of the experimental procedure for determining the formation of lymphatic vessels in the ear of a mouse using gelatin sponge. Figure 4 B is a gross observation diagram of the experiment on the formation of gelatin sponge lymphatic vessels in the mouse ear; Figure 4 C is a statistical chart showing the percentage of LYVE-1 immunofluorescence positive areas in the Control group, HA group, RC / HA group, dAM group, and RC / HA / dAM group; Figure 4 D shows the LYVE-1 immunofluorescence staining results of ear tissues from each group of mice.
[0062] In the picture, This indicates that p < 0.05. This indicates that p < 0.01. This indicates that p < 0.001. p < 0.0001, ns indicates that the difference is not statistically significant, i.e., p ≥ 0.05. Detailed Implementation
[0063] The various embodiments or implementation schemes in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments.
[0064] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with an embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0065] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0066] In this specification, unless otherwise specified, "parts" refers to "parts by weight".
[0067] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0068] Unless otherwise specified, hyaluronic acid and sodium hyaluronate have the same meaning in this application and are both represented by HA.
[0069] Preparation of recombinant collagen / sodium hyaluronate fiber membrane: Recombinant collagen (Zhejiang Zhuji Juyuan Biotechnology Co., Ltd., SFA02) and sodium hyaluronate (Bloomage Biotechnology Co., Ltd., nano-HA-cleaved oligomeric sodium hyaluronate, molecular weight <10kDa) were added to a 50% v / v ethanol aqueous solution, mixed and dissolved to prepare an electrospinning solution. The concentration of recombinant collagen in the electrospinning solution was 20% w / w, and the concentration of sodium hyaluronate was 4% w / w.
[0070] The obtained electrospinning solution was electrospinned using an HD-X1 electrospinning machine. During the electrospinning process, the positive voltage was set to 20 kV, the negative voltage was set to -5 kV, the injection speed was 0.05 mm / min, the receiving distance was 10 cm, and the obtained fibers were collected to obtain a recombinant collagen / sodium hyaluronate fiber membrane.
[0071] EDC and NHS were dissolved in anhydrous ethanol to prepare an EDC / NHS crosslinking solution with a molar ratio of 1:1 and a total concentration of 0.2 mol / L.
[0072] The recombinant collagen / sodium hyaluronate fiber membrane obtained in step S1 was immersed in the EDC / NHS crosslinking solution and crosslinked for 24 h. After crosslinking, the fiber membrane was washed with anhydrous ethanol and then vacuum dried to obtain the crosslinked recombinant collagen / sodium hyaluronate fiber membrane.
[0073] Preparation of decellularized amnion: Thaw the amniotic membrane stored in 85% (v / v) glycerol at ≤-60℃, remove it from the surgical sticker, place it in a culture dish, and wash it three times with purified water. Prepare a neutral protease (Maclean's, Dispase BR, 50 u / mg) working solution in 0.1 wt% serum-free medium or PBS. Add the enzyme solution to the centrifuge tube containing the amniotic membrane, ensuring the membrane is completely submerged. Incubate at 37℃ for 30 min. After incubation, scrape off the amniotic epithelium, place the amniotic membrane in purified water, and manually scrape off the epithelial cells until the amniotic membrane is transparent. Then wash it three times with purified water to obtain acellular amniotic membrane.
[0074] Example 1 Preparation of RC / HA / dAM lyophilized powder for promoting lymphatic vessel regeneration The detailed preparation flowchart is as follows: Figure 1 As shown in Figure A.
[0075] EDC and NHS were dissolved in PBS buffer (1×, pH=7.4) to prepare an EDC / NHS composite cross-linking solution with a concentration of 0.2 mol / L, wherein the molar ratio of EDC to NHS was 1:1.
[0076] Take a piece of decellularized amnion as the first decellularized amnion and lay it flat on silicone paper; lay a cross-linked recombinant collagen / sodium hyaluronate fiber membrane flat on top of the first decellularized amnion; take another piece of decellularized amnion as the second decellularized amnion and cover it on top of the cross-linked recombinant collagen / sodium hyaluronate fiber membrane, forming a three-layer structure consisting of the first decellularized amnion, the cross-linked recombinant collagen / sodium hyaluronate fiber membrane and the second decellularized amnion (the two sides of the cross-linked recombinant collagen / sodium hyaluronate fiber membrane are respectively attached to the matrix surface of the first decellularized amnion and the matrix surface of the second decellularized amnion).
[0077] The three-layer structure described above was immersed in an EDC / NHS composite crosslinking solution and mechanically pressed (3 kPa) on a pneumatic pressure machine platform. Crosslinking was performed under pressure for 48 h, allowing the first and second decellularized amniotic membranes to crosslink with the crosslinked recombinant collagen / sodium hyaluronate fiber membrane, respectively. After crosslinking, the membrane was washed with purified water, and the resulting material was freeze-dried in a freeze dryer to obtain the RC / HA / dAM composite membrane.
[0078] The dried RC / HA / dAM composite membrane was cut into fragments smaller than 6 mm and placed into the grinding jar of a cryogenic grinder.
[0079] Cryogenic grinding was performed using a 6775 cryogenic grinder. The pre-cooling time was 10 min; the running time and cooling time in each grinding cycle were 1 min and 3 min respectively; the grinding rate was 10 cps, and a total of 10 grinding cycles were performed.
[0080] After grinding, the grinding jar was removed from the cryogenic grinder and opened immediately. The resulting powder was quickly transferred to a centrifuge tube and sealed to obtain RC / HA / dAM composite microparticles.
[0081] Dissolve 20 mg of second sodium hyaluronate (Hybloom™ low molecular weight sodium hyaluronate, <1000 kDa) in 10 mL of purified water. Add 180 mg of RC / HA / dAM composite microparticles to the resulting second sodium hyaluronate solution and disperse using a disperser for 10 min to obtain an RC / HA / dAM composite microparticle suspension.
[0082] In the resulting suspension, the concentration of RC / HA / dAM composite microparticles was 18 mg / mL, the concentration of second sodium hyaluronate was 2 mg / mL, the total solids concentration was 20 mg / mL, and the mass ratio of RC / HA / dAM composite microparticles to second sodium hyaluronate was 9:1.
[0083] The resulting suspension was dispensed into 5 mL vials and freeze-dried in a freeze dryer to obtain RC / HA / dAM lyophilized powder for promoting lymphatic vessel regeneration.
[0084] When using, the obtained lyophilized powder can be rehydrated with 0.9% NaCl solution at a concentration of 20 mg / mL.
[0085] Comparative Example 1 HA freeze-dried powder A sodium hyaluronate solution was prepared using a second sodium hyaluronate and then freeze-dried to obtain HA lyophilized powder.
[0086] When using, rehydrate the obtained HA lyophilized powder with 0.9% NaCl solution at a concentration of 20 mg / mL.
[0087] Comparative Example 2 RC / HA lyophilized powder Cross-linked recombinant collagen / sodium hyaluronate fiber membranes were prepared according to the method in Example 1. The resulting fiber membranes were freeze-dried and then freeze-milled to obtain RC / HA microparticles.
[0088] Following the method in Example 1, the obtained RC / HA microparticles were dispersed in a second sodium hyaluronate solution under the same conditions, and then freeze-dried to obtain RC / HA lyophilized powder.
[0089] When using, rehydrate the obtained RC / HA lyophilized powder with 0.9% NaCl solution at a concentration of 20 mg / mL.
[0090] Comparative Example 3 dAM freeze-dried powder Following the method described in Example 1, the obtained decellularized amniotic membrane was freeze-dried and then freeze-milled to obtain dAM microparticles. The obtained dAM microparticles were then dispersed in a second sodium hyaluronate solution and freeze-dried to obtain dAM lyophilized powder.
[0091] When using, rehydrate the obtained dAM lyophilized powder with 0.9% NaCl solution at a concentration of 20 mg / mL.
[0092] Test section 1. Observation using scanning electron microscopy The lyophilized powders of HA, RC / HA, dAM and RC / HA / dAM obtained from Comparative Examples 1-3 and Example 1 were taken respectively, and the microstructure of each group of materials was observed by scanning electron microscopy.
[0093] The results are as follows Figure 1 As shown in B.
[0094] The HA lyophilized powder exhibits a loose and porous structure; in the RC / HA lyophilized powder, dAM lyophilized powder and RC / HA / dAM lyophilized powder, the corresponding particles are dispersed in the porous matrix formed by HA.
[0095] Further observation of the RC / HA / dAM lyophilized powder revealed that the decellularized amnion in the RC / HA / dAM composite microparticles was tightly bound to the RC / HA fiber structure. While preserving the original microstructure of the decellularized amnion, it was observed that the decellularized amnion was embedded in the network structure formed by the RC / HA fiber membrane. This indicates that after composite cross-linking, lyophilization, and freeze-milling, RC / HA and dAM can still maintain good structural integration.
[0096] 2. Particle size testing The particle size distribution of RC / HA particles, dAM particles, and RC / HA / dAM composite particles was determined using a laser particle size analyzer.
[0097] like Figure 1 As shown in C.
[0098] The results in the table show that the particle D50 of dAM alone after cryogenic grinding reached 169.050 μm, while the D50 of the RC / HA / dAM composite microparticles decreased to 66.446 μm, which is close to that of the RC / HA group. Meanwhile, the D90 of the RC / HA / dAM group was 170.008 μm, which is significantly lower than that of the dAM group (505.942 μm).
[0099] The above results indicate that natural decellularized amniotic membrane itself has good flexibility and is not prone to forming small particles when cryo-milled alone. When decellularized amniotic membrane is combined with cross-linked RC / HA fiber membrane to form a composite structure, its overall material properties change, making it easier for the resulting composite membrane to form smaller particles during cryo-milling. These smaller composite particles increase the contact between the material and surrounding cells and tissues, providing a suitable material morphology for its subsequent lymphatic regeneration-promoting effect.
[0100] 3. Cell compatibility of RC / HA / dAM lyophilized powder Human lymphatic endothelial cells (hLECs) were used to evaluate the cell compatibility of different materials.
[0101] Configure the following processing groups: Control group: 0.9% NaCl; HA group: HA lyophilized powder obtained from Comparative Example 1; RC / HA group: RC / HA lyophilized powder obtained from Comparative Example 2; dAM group: dAM lyophilized powder obtained from Comparative Example 3; RC / HA / dAM group: RC / HA / dAM lyophilized powder obtained in Example 1.
[0102] hLECs were co-cultured with each of the above groups of materials for 48 h.
[0103] a. TUNEL staining After co-culture, TUNEL staining was performed, and a positive control group treated with DNase I was set up.
[0104] The results are as follows Figure 2 As shown in Figure A, a significant TUNEL positive signal was observed in the DNase I positive control group, while TUNEL positive cells were extremely rare in the Control group and in the HA, RC / HA, dAM and RC / HA / dAM material groups.
[0105] b. Live / dead cell staining Live / dead cells were stained using calcein-AM / PI.
[0106] The results are as follows Figure 2 As shown in B, all groups of cells maintained normal cell morphology and mainly exhibited green fluorescence, while dead cells marked with red fluorescence were extremely rare.
[0107] Based on the combined results of TUNEL staining and live / dead cell staining, it can be seen that HA, RC / HA, dAM and RC / HA / dAM materials did not produce significant cytotoxicity to hLECs. Among them, the RC / HA / dAM lyophilized powder obtained in Example 1 has good cell compatibility and can provide a good biological basis for the subsequent proliferation, migration and tube formation of lymphatic endothelial cells.
[0108] 4. hLECs proliferation experiment The effects of each group of materials on the proliferation capacity of hLECs were evaluated using the BeyoClick™ EdU cell proliferation assay kit.
[0109] hLECs were co-cultured with 0.9% NaCl, HA, RC / HA, dAM and RC / HA / dAM for 48 h, respectively. EdU working solution was then added and incubated for another 3 h at 37℃ and 5% CO2. EdU staining was then performed and the proportion of EdU-positive cells was counted.
[0110] The results are as follows Figure 2 C and Figure 2 As shown in E.
[0111] The proportion of EdU-positive cells in the control group was 11.52%, while the proportion in the RC / HA / dAM group reached 22.21%, approximately 1.93 times that of the control group, and the difference between the two was statistically significant (p < 0.0001). Furthermore, the RC / HA / dAM group exhibited the highest proportion of EdU-positive cells among all material groups.
[0112] The above results demonstrate that the RC / HA / dAM lyophilized powder obtained in Example 1 can significantly promote hLEC proliferation. Combined with the cell compatibility results, it can be concluded that this proliferation effect does not originate from an abnormal response caused by the material damaging the cells, but rather enhances the proliferation capacity of hLECs while maintaining good cell compatibility.
[0113] 5. hLECs Transwell migration experiment Transwell experiments were used to evaluate the effects of different materials on the migration ability of hLECs.
[0114] 600 μL of culture medium containing 5% fetal bovine serum was added to the lower chamber of the Transwell, and 0.9% NaCl, HA, RC / HA, dAM and RC / HA / dAM materials were added respectively; hLECs resuspended in 1% fetal bovine serum culture medium were added to the upper chamber of the Transwell.
[0115] After 24 h of culture, crystal violet was used for staining, and cells that had not migrated in the upper chamber were wiped away with cotton swabs. The cells were then observed and photographed under an inverted microscope, and the number of cells that migrated to the lower surface in each field of view was counted.
[0116] The results are as follows Figure 2 D and Figure 2 As shown in F.
[0117] The average number of migrated cells was 17.33 per field of view; the average number of migrated cells in the dAM group increased to 78.33 per field of view; the RC / HA / dAM group further increased to 108.00 per field of view, which was about 6.23 times that of the Control group, and the RC / HA / dAM group still showed a significant difference compared with the dAM group (p < 0.001).
[0118] The above results indicate that dAM itself already possesses a significant hLEC migration-promoting effect. Furthermore, the RC / HA / dAM material obtained by combining dAM with RC / HA fiber structures according to the method described in this application further enhances the hLEC migration capability. This suggests that the effect of the RC / HA / dAM composite material is not simply a direct continuation of the existing biological activity of dAM, but rather a further enhanced migration-promoting effect achieved on the basis of dAM.
[0119] 6. hLECs scratch migration experiment hLECs were co-cultured with 0.9% NaCl, HA, RC / HA, dAM, and RC / HA / dAM for 48 h, respectively.
[0120] After culture, cells from each group were digested, resuspended, and seeded into 6-well plates. Once the cells had fully adhered to the plate, a straight scratch was made perpendicular to the bottom of the plate using a 200 μL pipette tip. Low-serum culture medium was then added, and images were acquired at the same location at 0 h, 6 h, and 12 h to calculate the scratch healing rate.
[0121] The results are as follows Figure 3 A and Figure 3 As shown in C.
[0122] Six hours after the scratch was applied, there was no statistically significant difference among the Control group, HA group, and RC / HA group (p>0.05); the scratch healing rate in the dAM group was 40.82%, significantly higher than that in the Control group (30.40%); and the RC / HA / dAM group further reached 47.94%.
[0123] Twelve hours after the scratch, the scratch healing rate in the RC / HA / dAM group reached 75.15%, which was higher than that in the dAM group (65.78%), the RC / HA group (59.04%), the HA group (54.81%), and the Control group (46.94%).
[0124] The scratch assay results and Transwell assay results corroborate each other, indicating that the RC / HA / dAM lyophilized powder obtained in Example 1 can significantly enhance the migration ability of hLECs. In particular, the RC / HA / dAM group further enhances the migration ability of dAM itself, which already has a strong ability to promote migration, further demonstrating that the composite structure of RC / HA and dAM is conducive to giving fuller play to the material's role in promoting the migration of lymphatic endothelial cells.
[0125] 7. hLECs tube formation experiment hLECs were co-cultured with 0.9% NaCl, HA, RC / HA, dAM, and RC / HA / dAM for 48 h, respectively.
[0126] After the culture was completed, the cells in each group were digested and seeded into culture dishes with pre-coated substrate gel at the bottom for further culture. The tubular networks formed at 2 h and 6 h of culture were observed, and the number of tube nodes and the total length of the tubular structure were counted.
[0127] The results are as follows Figure 3 B Figure 3 D and Figure 3 As shown in E.
[0128] After 2 h of culture, the Control group formed only a small number of sparse tubular structures; the HA, RC / HA and dAM groups all promoted the formation of early network structures of hLECs to varying degrees; the RC / HA / dAM group had the highest number of nodes and the highest total length of tubular structures, and both indicators were significantly higher than those of the Control group (p < 0.0001).
[0129] After 6 h of cultivation, the tubular networks in each group further developed, with both the number of nodes and the total length increasing. The RC / HA / dAM group maintained the highest number of nodes and total length, and both indicators were significantly higher than those in the Control group (p < 0.0001).
[0130] The above results demonstrate that the RC / HA / dAM lyophilized powder of this application can not only promote the proliferation and migration of hLECs, but also promote the formation of tubular networks by hLECs. Since the migration, proliferation, and tubular structure formation of lymphatic endothelial cells are all important steps in the process of lymphangiogenesis, the above in vitro results collectively indicate that the RC / HA / dAM material has good potential for promoting lymphangiogenesis.
[0131] 8. Experiment on lymphatic vessel formation in mouse ear using gelatin sponge To further evaluate the effects of different materials on promoting lymphangiogenesis in animals, a mouse ear gelatin sponge lymphangiogenesis model was used for testing. A schematic diagram of the experimental procedure for determining lymphangiogenesis in mouse ears is shown below. Figure 4 As shown in Figure A.
[0132] First, a 3mm diameter skin biopsy punch was used to prepare a 3mm diameter skin biopsy hole on a gelatin sponge. 3 Cylindrical gelatin sponge.
[0133] Each group of gelatin sponges was aspirated (supplementary intake) with 0.9% NaCl solution, HA, RC / HA, dAM, and RC / HA / dAM suspensions, and incubated at 37°C for 30 min. Subsequently, type I collagen solution was coated onto the surface of each group of gelatin sponges, and incubation was continued at 37°C for another 30 min.
[0134] Mice were anesthetized with isoflurane. A horizontal incision was made behind the ear of the mouse. The skin and cartilage behind the ear were carefully separated. A gelatin sponge containing each group of materials was implanted between the skin and cartilage behind the ear. The incision was then sutured.
[0135] Fourteen days after implantation, mouse ear tissue was harvested, embedded in OCT, and frozen sectioned. The ingrowth of lymphatic vessels inside the gelatin sponge was evaluated using LYVE-1 immunofluorescence staining.
[0136] The results are as follows Figure 4 As shown in B, 4C, and 4D.
[0137] Fourteen days after implantation, a certain degree of LYVE-1 positive signal was observed inside the gelatin sponge in the Control group and all material groups. The lymphatic vessel ingrowth area inside the Control group and HA group was relatively small; the lymphatic vessel ingrowth area in the RC / HA group and dAM group was increased compared with the Control group; among them, the RC / HA / dAM group showed the most obvious lymphatic vessel ingrowth, and its LYVE-1 positive area was significantly higher than that of other material groups.
[0138] The results of the animal experiments and in vitro experiments corroborate each other. Compared with the Control group, the dAM group already showed a promoting effect on lymphangiogenesis, indicating that the decellularized amniotic membrane itself has the potential to promote lymphatic vessel regeneration; the RC / HA / dAM group further showed a higher level of lymphatic vessel ingrowth, indicating that by using the method described in this application to combine dAM with cross-linked RC / HA fiber structures and further prepare them into lyophilized microparticles, the lymphatic vessel regeneration promoting effect of the material can be further improved.
[0139] The reasons for this are likely as follows: dAM can provide a natural extracellular matrix environment while retaining certain bioactive components; the cross-linked composite structure formed by the RC / HA fiber network and dAM helps maintain the structural stability of the composite microparticles, allowing them to continue acting on the local environment even after the membrane material is transformed into smaller particles; simultaneously, the composite microparticles have a smaller particle size than individual dAM particles, which helps increase the contact between the material and surrounding cells and tissues. Furthermore, the lyophilized matrix formed by the second sodium hyaluronate can support and disperse the resulting composite microparticles. These combined effects contribute to the fuller function of the RC / HA / dAM composite material in local tissues, thereby promoting lymphatic vessel regeneration.
[0140] Comprehensive analysis of test results: Based on the above test results, it can be seen that the RC / HA / dAM lyophilized powder obtained in Example 1 has good cell compatibility and can promote the biological behavior of hLECs from multiple stages of lymphatic vessel formation.
[0141] First, TUNEL staining and live / dead cell staining results showed that the RC / HA / dAM material did not produce significant cytotoxicity to hLECs, providing a basis for its further role in promoting lymphatic vessel regeneration.
[0142] Secondly, the EdU assay showed that the proportion of EdU-positive cells in the RC / HA / dAM group reached 22.21%, significantly higher than the 11.52% in the Control group. In the Transwell assay, the number of migrating cells in the RC / HA / dAM group reached 108.00 cells / field, significantly higher than the 17.33 cells / field in the Control group and the 78.33 cells / field in the dAM group. At 12 h after scratching, the scratch healing rate in the RC / HA / dAM group reached 75.15%, also higher than the 65.78% in the dAM group and other groups. These results indicate that the RC / HA / dAM lyophilized powder of this application can simultaneously enhance the proliferation and migration ability of hLECs.
[0143] Furthermore, the tube formation experiment showed that the RC / HA / dAM group exhibited a higher number of tube nodes and a higher total length of tubular structures at 2 h and 6 h of culture, indicating that it can promote the development of hLECs from proliferation and migration to the formation of tubular networks.
[0144] More importantly, the gelatin sponge experiment on mouse ears showed that the RC / HA / dAM group had the most obvious LYVE-1 positive lymphatic vessel ingrowth in the animals, proving that the above-mentioned in vitro proliferation, migration and vascularization effects can ultimately be transformed into in vivo lymphatic vessel regeneration effects.
[0145] Comparison of different material groups also revealed that dAM itself already exhibits significant effects in promoting hLEC migration and lymphangiogenesis, indicating that decellularized amniotic membrane is an important basis for the lymphatic regeneration effect of this application. However, the RC / HA / dAM group is superior to the dAM group in terms of hLEC proliferation, migration, tubule formation, and lymphatic vessel ingrowth in vivo. This indicates that this application does not only utilize the existing biological activity of decellularized amniotic membrane itself, but also further exerts its lymphatic regeneration potential by forming an integral composite structure with decellularized amniotic membrane and cross-linked RC / HA fiber membrane and further granulating it, making it more suitable for acting on the local environment in the form of microparticles.
[0146] Meanwhile, particle size analysis showed that the D50 of dAM after cryo-milling alone was 169.050 μm, while the D50 of the RC / HA / dAM composite microparticles decreased to 66.446 μm. This indicates that the combination of the RC / HA fiber network and dAM further improves the cryo-milling properties of the material, making it easier to form smaller composite microparticles. Combined with SEM results, it can be seen that while the particle size decreased, a good structural integration relationship between the dAM and RC / HA fiber structures was still observed in the RC / HA / dAM microparticles. This demonstrates that the "composite first, then granulated" processing method adopted in this application can balance the preservation of the composite structure and the microparticle formation, providing favorable conditions for the resulting material to fully contact cells in local tissues.
[0147] In summary, this application utilizes a decellularized amniotic membrane to form an RC / HA / dAM composite membrane with cross-linked recombinant collagen / sodium hyaluronate fiber membrane. After freeze-milling to form composite microparticles, these microparticles are further dispersed in a lyophilized sodium hyaluronate matrix. This allows the decellularized amniotic membrane, which promotes lymphatic vessel regeneration, to be used in a lyophilized microparticle form more suitable for local application. Experimental results, demonstrating from different perspectives including cell proliferation, migration, tubular formation, and lymphatic vessel ingrowth in animals, indicate that the RC / HA / dAM lyophilized powder of this application can effectively promote lymphatic vessel repair and regeneration.
[0148] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A lyophilized RC / HA / dAM powder for promoting lymphatic vessel regeneration, characterized in that, include: Sodium hyaluronate freeze-dried matrix, and RC / HA / dAM composite microparticles dispersed in the sodium hyaluronate freeze-dried matrix; The RC / HA / dAM composite microparticles are obtained by freeze-drying and freeze-milling of an RC / HA / dAM composite membrane. The RC / HA / dAM composite membrane comprises a first decellularized amnion, a cross-linked recombinant collagen / sodium hyaluronate fiber membrane, and a second decellularized amnion arranged sequentially, wherein the first decellularized amnion and the second decellularized amnion are chemically cross-linked with the cross-linked recombinant collagen / sodium hyaluronate fiber membrane, respectively.
2. The RC / HA / dAM lyophilized powder according to claim 1, characterized in that, The cross-linked recombinant collagen / sodium hyaluronate fiber membrane is obtained by electrospinning a spinning solution containing recombinant collagen and sodium hyaluronate to form a recombinant collagen / sodium hyaluronate fiber membrane, followed by chemical cross-linking of the fiber membrane.
3. The RC / HA / dAM lyophilized powder according to claim 2, characterized in that, The molecular weight of the first sodium hyaluronate is less than 10 kDa; the concentration of recombinant collagen in the spinning solution is 15-25% w / w, the concentration of the first sodium hyaluronate is 3-5% w / w, and the solvent of the spinning solution is a 40-60% v / v aqueous ethanol solution.
4. The RC / HA / dAM lyophilized powder according to claim 2, characterized in that, The recombinant collagen / sodium hyaluronate fiber membrane was cross-linked using EDC / NHS, with a molar ratio of EDC to NHS of 1:(0.8-1.2) and a cross-linking time of 20-28 h.
5. The RC / HA / dAM lyophilized powder according to claim 1, characterized in that, The second sodium hyaluronate used to form the lyophilized sodium hyaluronate matrix has a molecular weight of less than 1000 kDa, and the mass ratio of the RC / HA / dAM composite microparticles to the second sodium hyaluronate is (8-10):
1.
6. A method for preparing RC / HA / dAM lyophilized powder for promoting lymphatic vessel regeneration, characterized in that, Includes the following steps: S1: The cross-linked recombinant collagen / sodium hyaluronate fiber membrane is placed between the first decellularized amnion and the second decellularized amnion, and is pressed in a chemical cross-linking system to cross-link the decellularized amnion with the cross-linked recombinant collagen / sodium hyaluronate fiber membrane to obtain the RC / HA / dAM composite membrane. S2: The RC / HA / dAM composite membrane is freeze-dried and then freeze-milled to obtain RC / HA / dAM composite microparticles; S3: After dispersing the RC / HA / dAM composite microparticles in a second sodium hyaluronate solution to form a suspension, the suspension is freeze-dried to obtain RC / HA / dAM freeze-dried powder for promoting lymphatic vessel regeneration.
7. The method according to claim 6, characterized in that, S1 includes placing a cross-linked recombinant collagen / sodium hyaluronate fiber membrane between a first decellularized amnion and a second decellularized amnion, and immersing it in an EDC / NHS cross-linking system, and performing cross-linking under mechanical compression for 40-60 hours; the molar ratio of EDC to NHS is 1:(0.8-1.2).
8. The method according to claim 6, characterized in that, In step S2, the RC / HA / dAM composite membrane is freeze-dried, cut into fragments smaller than 6 mm, and then cryogenically ground. The cryogenic grinding includes pre-cooling for 8 to 15 minutes and grinding 8 to 15 times at a rate of 8 to 15 cps, with each cycle lasting 0.5 to 1.5 minutes and followed by 2 to 4 minutes of cooling.
9. The method according to claim 6, characterized in that, In S3, the mass ratio of RC / HA / dAM composite microparticles to second sodium hyaluronate in the suspension is (8-10):1, and the total solid concentration is 15-25 mg / mL.
10. Use of the RC / HA / dAM lyophilized powder according to any one of claims 1 to 5 or the RC / HA / dAM lyophilized powder prepared by the method according to any one of claims 6 to 9 in the preparation of formulations for promoting lymphatic vessel regeneration.